Pimento : the Jamaican allspice story - Gayle, John (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
This book is on Pimento otherwise known to the spice world as Jamaican Allspice, one of Jamaica’s oldest export commodities. It is the most informative and comprehensive book to be written on the subject and the most recent publication that readers will find on the agricultural shelf of any library. Some of its contents are extracts from previous publications issued many decades ago by various scientific institutions and agricultural researchers including the Agricultural Planning Unit of the Ministry of Agriculture and Fisheries, the Botany and Chemistry Departments of the University of the West Indies, the then Tropical Products Institute of London, the Plant Protection Division of the Ministry of Agriculture, a Chief Agricultural Officer, a horticulturalist and a Miscellaneous Fruit Tree Specialist of the Crops and Soils Department of the Ministry.